Pola konsumsi dan investasi di Indonesia : Tren, perubahan , dan implikasinya terhadap ekonomi - Alfina, Fayyadho Tahtah (Maliki Interdisciplinary Journal, 2025)
Consumption and investment patterns in Indonesia have experienced significant changes in the last few decades, influenced by various factors such as economic growth, demographic changes and government policies. Domestic consumption, which has been the main driver of Indonesia's economic growth, is increasingly transforming with the rise of the middle class and a shift in consumption preferences towards digital products and modern services. On the other hand, investment, both domestic and foreign, continues to grow with a focus on the infrastructure, technology and renewable energy sectors. This trend is accelerated by digitalization and global economic integration, creating new opportunities for strategic sectors. However, high dependence on household consumption makes the Indonesian economy vulnerable to external shocks, while geographically unequal investment widens gaps between regions. The implications of these changes for the national economy are very significant, with prospects for more inclusive and sustainable growth if the government succeeds in balancing consumption and investment through policies that support the development of the productive sector, increasing the competitiveness of the workforce, and equitable development. Abstract in Indonesian.